2020
DOI: 10.1029/2019jc015716
|View full text |Cite
|
Sign up to set email alerts
|

A New Algorithm for Sea Ice Melt Pond Fraction Estimation From High‐Resolution Optical Satellite Imagery

Abstract: Melt ponds occupy a large fraction of the Arctic sea ice surface during spring and summer. The fraction and distribution of melt ponds have considerable impacts on Arctic climate and ecosystem by reducing the albedo. There is an urgency to obtain improved accuracy and a wider coverage of melt pond fraction (MPF) data for studying these processes. MPF information has generally been acquired from optical imagery. Conventional MPF algorithms based on high-resolution optical sensors have treated melt ponds as feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The LinearPolar Algorithm by Wang et al (2020) was developed for small subsets (less than 2 km edge length) of Sentinel-2 scenes to extract MPF from the optical imagery. We adopt the fundamental approach and introduce changes to make the algorithm applicable to larger subsets (larger than 50 km length) and a wider variability of scenes.…”
Section: Classification Of Sentinel-2 Imagerymentioning
confidence: 99%
See 3 more Smart Citations
“…The LinearPolar Algorithm by Wang et al (2020) was developed for small subsets (less than 2 km edge length) of Sentinel-2 scenes to extract MPF from the optical imagery. We adopt the fundamental approach and introduce changes to make the algorithm applicable to larger subsets (larger than 50 km length) and a wider variability of scenes.…”
Section: Classification Of Sentinel-2 Imagerymentioning
confidence: 99%
“…The algorithm is based on the bands 2 (B2 ) and 8 (B8 ) of the Sentinel-2 instrument with central wavelengths of 490 nm and 842 nm, respectively. This is because of the significant difference between the spectral behavior of ice, melt pond and open water surfaces at these wavelengths (Rösel et al, 2012;Wang et al, 2020).…”
Section: Classification Of Sentinel-2 Imagerymentioning
confidence: 99%
See 2 more Smart Citations
“…Most recent measurements on melt ponds concentrated on the horizontal scale, such as melt pond fraction and size [4][5][6], whereas with the development of numerical models, more and more studies demonstrated that H p and H i are the key factors that affect the optical properties of melt pond. For example, Lu et al [7] confirmed that the melt pond albedo increases mainly with H i for thin ice (H i < 1 m), while it depends on H p and H i for ice thickening, and finally chiefly on H p for H i > 3 m. The transmittance was dependent only on H i .…”
Section: Introductionmentioning
confidence: 99%